A remarkable new species of Empidideicus (Diptera: Mythicomyiidae) from Madagascar - Evenhuis, Neal L. (Zootaxa, 2007)
A new species of Empidideicus, E. rhinoclypeatus, n. sp. from Madagascar is described and illustrated. It marks the first published description of a species of the genus from Madagascar. The new species is noteworthy in that it possesses a remarkable elongation of the clypeus. A key to species of Empidideicus from southern Africa, Sokotra, and Madagascar is presented.